Роль компетенції місцевого самоврядування у становленні локального сталого розвитку - Баймуратов, М.М. (Інститут держави і права ім. В.М. Корецького НАН України, 2009)
Исследуются актуальные вопросы совершенствования и развития компетенции местного самоуправления, его субъектов и органов, ее влияние на процессы местного устойчивого развития. In the article the actual questions of perfection and development of jurisdiction of local self-government, his subjects and organs, are probed, its influence on the processes of local steady development.